Image cytometry analysis of normal buccal mucosa smears: influence of smoking and sex-related differences - Lavrenčak, Jaka (Radiology and oncology (Ljubljana), 1998)
To get more information about the influence of smoking on chromatin pattern ofnormal buccal mucosa cells and to assess sex-related differences in nuclear features, quantitative analysis of normal buccal mucosa smears was performed. In this study, buccal smears were collected from 78 healthy subjects. Image cytometry analysis was performed on Feulgen-thionin stained smears. probability distributions of 78 nuclear features were calculated for both, cell-by-cell and slide-by-slide classifications. Seven nuclear features showeddiscriminative ability between smokers and non-smokers; most of them were nuclear texture features. Statistical analysis of nuclear features in groups of females and males hoswed that only two nuclear features were different. It is concluded that smoking should be considered in image cytometry analysis of lesions in oral cavity.
Keywords: analiza; Cell nucleus; diagnostika; fiziologija; Image cytometry; kajenje; Mouth mucosa; Sex factors; sluznica; Smoking; ustna votlina